`BERBANTUAN COPILOT AI KELAS XII DI SMAN 1 PERCUT SEI TUAN - Adzkia Rizkianisa Awira Siregar; Aanisah Nadya Shafwah; Eveline Stephani; Fadhylah Zaini Pardede; Khoirun Nisa; Trisnawati Hutagalung; Nurul Azizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop innovative teaching materials on main ideas and supporting details assisted by Copilot AI for twelfth-grade students at SMAN 1 Percut Sei Tuan as an effort to improve students’ reading literacy skills in the digital era. This research employed a Research and Development (R&D) model using the ADDIE approach, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through observations, interviews, questionnaires, and expert validation. The validation results from material and media experts showed a feasibility percentage of 93% categorized as very valid, while the trial conducted on 30 students yielded a practicality score of 85%, indicating that the Copilot-AI-assisted teaching materials effectively supported students in understanding main ideas and supporting details. The findings of this study confirm that the use of Copilot AI enhances conceptual understanding, facilitates more interactive learning, and serves as a relevant and adaptive alternative learning medium in Bahasa Indonesia instruction.